Predictors of Weight Change: Findings From an Employee Wellness Program - Feldman, Sue S.; Cochran, Randyl A.; Mehta, Tapan (Frontiers in Endocrinology, 2019)
Introduction: Employers are instituting employee wellness programs that include educational, lifestyle coaching, and weight and other condition management components to address obesity-related issues in the workplace. However, the findings of such wellness initiatives have been mixed. The purpose of this exploratory study is to determine whether the readiness for change measures are important predictors of weight loss in an employee wellness program. Methods: Retrospective data analysis of an employee wellness program conducted in the United States was conducted using data collected between 2014 and 2015 for people with BMI>=30. These participants were assigned to one of two subprograms: weight management or condition management. The relationship between weight change and readiness for change variables for weight, diet and physical activity were examined by applying multiple linear regression and logistic regression models. The multivariable model included subprogram; gender; age; systolic and diastolic blood pressure; risk factor count; readiness for change for weight, activity, and diet; and stress level as covariates. Results: On average, the weight change in this group was -0.28 pounds (SD= 15.55). When compared to the reference group (maintenance), participants at the action stage of physical activity, on average, lost weight (b= -4.67, p= 0.018). Likewise, participants at the pre-contemplation stage of physical activity lost weight when compared to the maintenance group (b= -26.402, p= 0.000). However, when the readiness for change diet variable was examined, participants at the pre-contemplation stage gained weight when compared to the maintenance group (b= 40.334, p= 0.002). Participants at the pre-contemplation stage of physical activity had marginally higher odds of achieving at least 5% weight loss than participants at the maintenance stage (OR= 5.802, p= 0.053). Conclusion: Readiness for change for activity and diet are predictors of weight change, and readiness for change in activity predicts the likelihood of achieving clinically significant weight loss. These findings can assist in targeting subjects for participation in such programs. The findings regarding the relationship between readiness for change and weight loss are counterintuitive, and further research is warranted in this area.